Functional and anatomical deficits in visceral nociception with age: a mechanism of silent appendicitis in the elderly?. Issue 4 (April 2020) - Cibert-Goton, Vincent; Kung, Victor W.S.; McGuire, Cian; Hockley, James R.F.; Tranter, Michael M.; Dogra, Harween; Belai, Abi; Blackshaw, L. Ashley; Sanger, Gareth J.; Knowles, Charles H.; Araujo, Eduardo J.A.; Winchester, Wendy J.; et al.
Abstract : Abstract: The ability to sense visceral pain during appendicitis is diminished with age leading to delay in seeking health care and poorer clinical outcomes. To understand the mechanistic basis of this phenomenon, we examined visceral nociception in aged mouse and human tissue. Inflamed and noninflamed appendixes were collected from consenting patients undergoing surgery for the treatment of appendicitis or bowel cancer. Supernatants were generated by incubating samples in buffer and used to stimulate multiunit activity in intestinal preparations, or single-unit activity from teased fibres in colonic preparations, of young and old mice. Changes in afferent innervation with age were determined by measuring the density of calcitonin gene-related peptide-positive afferent fibres and by counting dorsal root ganglia back-labelled by injection of tracer dye into the wall of the colon. Finally, the effect of age on nociceptor function was studied in mouse and human colon. Afferent responses to appendicitis supernatants were greatly impaired in old mice. Further investigation revealed this was due to a marked reduction in the afferent innervation of the bowel and a substantial impairment in the ability of the remaining afferent fibres to transduce noxious stimuli. Translational studies in human tissue demonstrated a significant reduction in the multiunit but not the single-unit colonic mesenteric nerve response to capsaicin with age, indicative of a loss of nociceptor innervation. Our data demonstrate that anatomical and functional deficits in nociception occur with age, underpinning the atypical or silent presentation of appendicitis in the elderly. Abstract : Supplemental Digital Content is Available in the Text.Visceral nociception is diminished with age in mouse and human tissue, due to a loss of innervation, and impaired stimulus transduction in remaining nociceptors.